IMPACTS DURING LANDING IN DIFFERENT SPORTS (Fiep Bulletin - online, 2014)
The aim of this study was to identify the impacts during landings and to correlate these impacts with kinematics variables referred to the movement technique. The study was performed with three groups of athletes (volleyball - VB, basketball - BB and indoor soccer - FS) and a group of non-athletes (NA). The volunteers performed maximal Countermovement Jumps on a force plate. Beyond the dynamic analysis the indoor soccer group was submitted to a kinematic analysis. No significant differences between the groups VB, BB and NA concerning the impacts magnitude could be found. 40% of the volleyball players and 50% of the basketball players and non-athletes have mean impacts higher than 5 x body weight. This indicates an inadequate landing strategy. The group FS produced significantly higher impacts than the other groups. The time from the first contact to the highest impact was significantly different between the landings with low impacts (0,066 ± 0,01ms) and landings with high impacts (0,048 ± 0,01ms), as well as the angle of the ankle at the first contact (127,5º ± 3,6º) and (121,3º ± 10,8) in landings with low and high impacts, respectively. It can be concluded that an adequate movement technique can reduce maximal impacts and injury risk.
Keywords: impacts; movement technique; injuries